STUDI DESKRIPTIF PROFIL ANTROPOMETRI DAN STATUS GIZI PADA BALITA SAKIT DI PMB PERMATA HATI MATESIH - Agustin, Kurnia; Suwarnisih (Jurnal Ilmiah Maternal, 2025)
Toddlers represent a highly vulnerable population to health and nutritional problems due to their rapid growth and development phase. Adequate nutritional status plays a critical role in supporting optimal physical growth, cognitive development, and immune function, thereby enhancing resistance to disease. In contrast, poor nutritional status can increase susceptibility to illness, prolong recovery, and elevate the risk of complications and mortality, particularly among toddlers who are already ill. This study aimed to determine the distribution of nutritional status among ill toddlers so that the findings may serve as baseline information for growth monitoring, nutritional intervention planning, and improvement of the quality of health and nutrition services at PMB Permata Hati Matesih. A quantitative descriptive retrospective cohort design was applied, using total sampling and secondary data collected from January to June 2025. The results showed that 9.52% of toddlers were classified as severely undernourished, 19.05% as undernourished, 69.05% had normal nutritional status, and 2.38% were overweight. These findings indicate that although most ill toddlers had normal nutritional status, a substantial proportion still experienced nutritional problems that require attention. Therefore, future research is recommended to employ analytical or longitudinal designs to further examine causal relationships between nutritional status, frequency of illness, and the effectiveness of pharmacological and complementary therapies in toddlers.. Keywords: Anthropometry; Nutritional Status; Sick Toddlers